FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN PROTOKOL KESEHATAN 3M (MEMAKAI MASKER, MENCUCI TANGAN, MENJAGA JARAK) - Aries Chandra Anandhita; Siswanto Agung Wijaya; Jihan Fachriyah Hasany (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Background: The global health problem that is currently the world's attention and spotlight is Covid-19. Infectious diseases caused by Severe Acute Respiratory Syndrome Coronavirus-2 and the spread of the Covid-19 virus are one of the causes of the current high mortality rate. The 3M health protocol is very influential in breaking the chain of transmission of Covid-19, especially among teenagers. The purpose of this study was to determine the factors associated with the application of the 3M health protocol (Wearing Masks, Washing Hands, and Keeping Distance) in MA Muhammadiyah 04 Ujungpangkah Gresik Students.Â Methods: This study used a descriptive correlational research design with cross sectional. With a total population and sample of 78 respondents using a total sampling technique with independent variables including knowledge, attitudes, availability of infrastructure, and environmental support, the dependent variable is the application of the 3M health protocol. The instruments used in this research are questionnaires and observations that have been tested for validity and reliability by using the Spearman Rank correlation analysis test.Â Results: The results of the Spearman Rank correlation test showed that, there was a relationship between knowledge and the application of the 3M health protocol (p=0.000), there was a relationship between attitude and the application of the 3M health protocol (p=0.023), there was a relationship between infrastructure and the application of the 3M health protocol (p=0.000) ), and there was a relationship between environmental support and the implementation of the 3M health protocol (p=0.012).Â Suggestion: The advice given to students is that with good infrastructure, it is hoped that students can improve their behaviour in implementing the 3M health protocol properly and correctly as an effort to prevent infectious diseases.